2011
DOI: 10.1021/mp100397p
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Delivery into Tumor Cells with Ultrasound and Microbubbles

Abstract: Doxorubicin is a potent chemotherapeutic whose severe side effects limit its application. Drug-targeted delivery with noninvasive techniques is required to increase the drug concentration locally and to reduce systemic side effects. Microbubble-assisted ultrasound has become a promising strategy for noninvasive local drug delivery. The aim of this study is to evaluate the applicability and the effectiveness of administration of doxorubicin combined with microbubble-assisted ultrasound in human U-87MG glioblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 34 publications
5
99
1
Order By: Relevance
“…''Sonoporation'' (117; 2.4 %) has an apparent upward movement in its ranks, from no emergence in 1991-1996 to 9th in 2009-2014. Further, with the introduction of microbubble-assisted ultrasound, a phenomenon called sonoporation has been successfully applied to deliver drugs and genes in vitro and in vivo in a variety of therapeutic application (Ferrara et al 2007;Escoffre et al 2011;Delalande et al 2013). In addition, ''Cavitation'' (139; 2.9 %) in author keywords steadily ranked in the top 11 during all four 6-year periods, which illustrates that ultrasound-induced microbubble cavitation has been an on-going concern (Doida et al 1998;Postema et al 2004;Zhang et al 2013).…”
Section: Author Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…''Sonoporation'' (117; 2.4 %) has an apparent upward movement in its ranks, from no emergence in 1991-1996 to 9th in 2009-2014. Further, with the introduction of microbubble-assisted ultrasound, a phenomenon called sonoporation has been successfully applied to deliver drugs and genes in vitro and in vivo in a variety of therapeutic application (Ferrara et al 2007;Escoffre et al 2011;Delalande et al 2013). In addition, ''Cavitation'' (139; 2.9 %) in author keywords steadily ranked in the top 11 during all four 6-year periods, which illustrates that ultrasound-induced microbubble cavitation has been an on-going concern (Doida et al 1998;Postema et al 2004;Zhang et al 2013).…”
Section: Author Abstractmentioning
confidence: 99%
“…Figure 9c shows that cell, cancer, drug, gene, liver and myocardial related research are the most common topics in micro/nano-bubble related research (Bax et al 2003;Ferrara et al 2007;Escoffre et al 2011;Delalande et al 2013). Cell-related research has attained a tremendous increase in popularity and dominated the research focus since 2005.…”
Section: Hot Issues and Future Trendsmentioning
confidence: 99%
“…To overcome these problems, the development of an efficient, safe and targeted delivery of irinotecan is required to reduce the therapeutic dose. Recent research has demonstrated that targeted drug delivery using ultrasound (US) combined with microbubbles, also known as sonoporation, offers new opportunities to improve the therapeutic effectiveness of tumor treatment and to reduce toxic exposure to healthy tissues 4,5 . Microbubbles under US activation oscillate and increase the permeability of biological barriers facilitating thus the drug extravasation into the treated tissue 6 .…”
mentioning
confidence: 99%
“…Extensive and recent analyses of these promising strategies can be found [37,38]. Third, the penetration of drug (or genetic material) into cells can be enhanced by the process of sonoporation [39][40][41][42]. Finally, the amount of drug available in the targeted tissue can be increased by facilitating the crossing of a physiological barrier, as in the case of the blood-brain barrier [43].…”
Section: Mechanisms Of Ultrasound-mediated Drug Deliverymentioning
confidence: 99%